Configuration of prosocial motivations to enhance employees’ innovation behaviors: From the perspective of coupling of basic and applied research - Lu, Yuting; Zheng, Linlin; Zhang, Binghua; Li, Wenzhuo (Frontiers in Psychology, 2022)
Prosocial motivation refers to the employees’ willingness to invest for the sake of helping others. It improves basic and applied research behaviors of employees and the interaction between them. Employees’ innovation behavior depends on the prosocial motivation, because the motivation to protect the interests of others may promote knowledge sharing and knowledge coupling. However, there is a research gap on solving the optimal solution of prosocial motivations that facilitates different types of innovation behaviors based on the combination of prosocial motivations. We perform a qualitative comparative study on the effect of the motivation configurations on innovation behaviors. We find that highly basic and highly applied research behaviors share in common collectivism-based, principlism-based, contextual, and situational motivations which work in all configurations. But the core conditions between the two is different, which are principlism-based and situational motivations respectively. In addition, both of highly basic-to-applied and highly applied-to-basic transformation behaviors share the same core condition and the same secondary conditions with highly basic and highly applied research behaviors respectively. Moreover, the behaviors of non-highly basic research and non-highly basic-to-applied transformation share the severe absence of the egoism-based motivation as the core condition in common. Non-highly behaviors of applied research and applied-to-basic transformation have the common point of the severe absence of the pressure-based type as the key. Finally, we also analyze active and passive prosocial degree of all types of high/non-high innovation behaviors. Our study deepens the academic’s thinking on multi-dimensional prosocial motivation and the classification management of coupling innovation behavior, and provides implications for practice.